Periprocedural Management during Placement of Flow Diverters in Intracranial Aneurysms: A Clinical Report and Review of Literature - Mishra, Rajeeb K.; Mahajan, Charu; Kapoor, Indu; Prabhakar, Hemanshu (Journal of Neuroanaesthesiology and Critical Care, 2019)
Background Placement of flow diverter (FD) is an endovascular technique where the flow to the aneurysm is directed away from the aneurysmal sac using a stent in the parent vessel. In this clinical report, the authors share their institutional experience pertaining to clinical course of patients with intracranial aneurysm requiring placement of FD.Methods After approval from institute ethics committee (IEC), the authors retrospectively studied all patients who underwent placement of FD for intracranial aneurysms from January 2014 to December 2017. Data regarding patient demographics, presenting complaints, aneurysm details, anesthesia technique, and intra- and postprocedural complications were noted. Duration of hospital stay, neurological outcome as measured by Glasgow outcome scale (GOS) at discharge and at 6 months was noted. Data are presented as median (range) or number (%).Results Over a period of 3 years, 22 patients underwent FD placement. Two patients had subarachnoid hemorrhage (SAH) at the time of presentation, and the rest had unruptured aneurysms. All patients received general anesthesia (GA) for the procedure, and intravenous propofol was used for induction of anesthesia. Majority of the patients received sevoflurane and nitrous oxide combination for maintenance of anesthesia (20/22 [91%]). Five patients were not extubated at the end of the procedure. The most common indication for mechanical ventilation was delayed reversal because of hypothermia. At 6 months of follow-up, GOS was 5 in 18 patients. None of the patients developed any delayed complications related to FD and were neurologically intact.Conclusions The use of FD for the treatment of aneurysms is a safe option. GA was used for carrying out procedure in all patients. The neurological outcome was good in all patients who were followed at 6 months.
Keywords: flow diverter; anesthetic management; intracranial aneurysms